UNDERPLANTING OF YOUNG COCONUTS UNDER ADULT STANDS OF COCONUT PALMS FOR PRODUCTION OF EDIBLE VEGETATIVE PITH OR 'UBOD' - Gerardo D. Padrones; Millicent I. Secretaria; Severino S. Magat (International Coconut Community Journal, 1999)
The feasibility and viability of producing edible vegetative coconut pith or 'ubod' from young coconuts planted with double plants per hill under adult coconut bearing palms was studied at the Philippine Coconut Authority - Davao Research Center, Bago Oshiro Davao City. The average weight of 'ubod' from double planting scheme was 5.9 kg/palm (range 2.8 -9.4 kg) on the first year of 'ubod' harvest. There was a very slight increase (average of 0.2 kg/palm) in 'ubod' weight on the second year of harvest. The total ubod yield for two years harvesting schedule was 8.9 t/ha. Under the Davao growing condition, cost and return analysis of 'ubod' production in double plants per hill scheme indicated a total net income of P129,030 per ha in 4 years with a return on investment (ROI) of 180%. While copra production from adult bearing palms realized a total of P 114,675 for 4 years with an average ROI of 242%. Considering copra plus 'ubod' yield from this production scheme, the cumulative net income and ROI obtained were: P 242,389.6 and 203% respectively. Based on the results of this study with modest fertilizer application of ammonium sulfate plus common salt (NaCl), underplanting of two young coconuts per hill (spaced at two feet away from each other) at 3 x 3 m distance between spaces of bearing coconut palms harvested at three years from field-planting is a profitable and viable production scheme to increase farm productivity. The farm income with this coconut-based production is increased by 200% compared to coconut monocropping.